Pembelajaran Menulis Bahasa Arab di Program Khusus Perkuliahan Bahasa Arab (PKPBA) Universitas Islam Negeri Malang - Oktavia Ratnaningtyas (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
Language is the main tool used in learning, without learning the language will not run properly. Likewise in understanding literature and books required a good language so that they can understand it well too. Writing skills are mahârah al-ibtikâriyah or writing skill is the ability to describe or disclose the contents of the mind, ranging from simple aspects such as writing words that are simple to complex aspect is fabricated. The text below trying to unravel the curriculum, the problems and solutions of the learning Arabic writing college level that have a special program of lectures Arabic.